2016
DOI: 10.1371/journal.pone.0157238
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Sleep Quality as a Possible Mediator in the Relationship between Personality Traits and Depressive Symptoms in Middle-Aged Adults

Abstract: This study explored the mediating role of sleep in the relationship between personality traits and depressive symptoms in a group of community-dwelling men and women (Mage = 57.92, SD = 4.00). Participants completed the short form NEO Five Factor Inventory (NEO-FFI), Pittsburgh Sleep Quality Index (PSQI), and the Center for Epidemiologic Studies Depression Scale (CES-D). High neuroticism and low conscientiousness was associated with poor sleep, as well as greater depressive symptom severity. Partial indirect m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…In terms of the relationships between sleep quality, affects, and LS, the findings were consistent with those of the literature: Better sleep quality was associated with less NA (Bower et al, 2010;Huang et al, 2016), more PA (Bower et al, 2010;Mccrae et al, 2008), and greater LS (Paunio et al, 2009). These findings can probably be explained by the experimentally observed link between sleep loss and mood regulation deficits (Yoo et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…In terms of the relationships between sleep quality, affects, and LS, the findings were consistent with those of the literature: Better sleep quality was associated with less NA (Bower et al, 2010;Huang et al, 2016), more PA (Bower et al, 2010;Mccrae et al, 2008), and greater LS (Paunio et al, 2009). These findings can probably be explained by the experimentally observed link between sleep loss and mood regulation deficits (Yoo et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, 6-month persistence of poor sleep directly predicted drive for thinness and bulimia, and indirectly predicted body dissatisfaction and drive for thinness via depression. Another study reported that CES-D scores were related to global PSQI in a community sample [ 30 ]. In contrast, we evaluated the sleep quality of patients with AN at a single point in time and focused on purging behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies that have more generally focused on normal personality traits and sleep complaints also find neuroticism to predict reports of poor sleep quality or interrupted sleep, regardless of demographic factors (Cellini, Duggan, & Sarlo, ; Duggan, Friedman, McDevitt, & Mednick, ; Gray & Watson, ; Hintsanen et al, ; Soehner, Kennedy, & Monk, ; Williams & Moroz, ). Low conscientiousness (and high impulsivity) has also been linked to reports of poor sleep, although its ties are weaker and less consistent than those of neuroticism and depression (Cellini et al, ; Granö et al, ; Huang, Peck, Mallya, Lupien, & Fiocco, ; Kim et al, ). Regarding other traits, extraversion and especially positive affectivity have been linked to reports of somewhat better sleep, while agreeableness and openness show weak or inconsistent relations (Cellini et al, ; Duggan et al, ; Gray & Watson, ; Williams & Moroz, ).…”
Section: Sleep and How It Workmentioning
confidence: 99%
“…On one hand, these findings clearly implicate personality as important for sleep; more neurotic individuals are at a greater risk for developing insomnia, report worse and declining sleep quality as do less conscientious individuals, and may be at an increased risk for depression due to distress about their sleep (Huang et al, ; Singareddy et al, ; Stephan et al, ). On the other hand, existing evidence does not speak to important questions about how core features of sleep link to personality.…”
Section: Sleep and How It Workmentioning
confidence: 99%